2011
DOI: 10.1111/j.1755-5922.2011.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beta‐Blockade on Exercise Performance at High Altitude: A Randomized, Placebo‐Controlled Trial Comparing the Efficacy of Nebivolol versus Carvedilol in Healthy Subjects

Abstract: SUMMARYAims: Exposure to high altitude (HA) hypoxia decreases exercise performance in healthy subjects. Although β-blockers are known to affect exercise capacity in normoxia, no data are available comparing selective and nonselective β-adrenergic blockade on exercise performance in healthy subjects acutely exposed to HA hypoxia. We compared the impact of nebivolol and carvedilol on exercise capacity in healthy subjects acutely exposed to HA hypobaric hypoxia. Methods: In this double-blind, placebo-controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
0
20
0
3
Order By: Relevance
“…Of note, the reduced exercise performance during HA exposure, similar to what has been shown in HF patients, may be favorably modulated by selective beta1-blockers such as bisoprolol and nebivolol (Valentini et al, 2012;Agostoni, 2013).…”
Section: Effects Of Aging On Blood Pressure and Its Regulation At Higmentioning
confidence: 81%
See 1 more Smart Citation
“…Of note, the reduced exercise performance during HA exposure, similar to what has been shown in HF patients, may be favorably modulated by selective beta1-blockers such as bisoprolol and nebivolol (Valentini et al, 2012;Agostoni, 2013).…”
Section: Effects Of Aging On Blood Pressure and Its Regulation At Higmentioning
confidence: 81%
“…Hypoxia is a potent sympathetic activator via stimulation of the peripheral chemoreceptors, as demonstrated by the increase in heart rate and plasma norepinephrine observed in this condition (Wolfel et al, 1994). Similarly, in the placebo group of HIGHCAREHimalaya study, noradrenaline showed a marked progressive increase with exposure to the 3400 and 5400 m altitudes, with a tendency to return to baseline values upon return to sea level (Valentini et al, 2012;Agostoni et al, 2013;Parati et al, 2014a) (Fig. 5).…”
Section: Physiological Mechanisms Underlying Bp Responses To High Altmentioning
confidence: 88%
“…This did not translate into improved exercise capacity; however, it did not result in any adverse effect nor in a reduction of physical performance. This is at variance from other antihypertensive drugs suggested to be used at altitude, such as some beta blockers, that may have a negative impact on ventilatory control and exercise capacity in hypoxic conditions 25, 26, 27. Moreover, the slope of the VO 2 /work relationship was unaffected by high altitude (3260 m) both in the active treatment group and in the placebo group, suggesting that during effort, compensatory mechanisms allow oxygen delivery to muscles to remain stable.…”
Section: Discussionmentioning
confidence: 99%
“…Differently, it is now appreciated that the exercise performance of healthy subjects at high altitude is influenced by the type of b-blocker used. In a recent report, Valentini et al (2011) showed that at Capanna Regina Margherita (4560 m) peak Vo 2 was lower in healthy subjects treated with carvedilol (b 1 -b 2 receptor blocker) than in those on nebivolol (a selective b 1 receptor blocker). This difference was related to a greater peak exercise ventilation at altitude with nebivolol versus carvedilol.…”
Section: Introductionmentioning
confidence: 96%